이론적 방법에 의한 제습로터 최적 회전속도의 결정 - 이대영; 송귀은 (대한설비공학회, 2009)
The optimum rotation speed of a desiccant rotor is studied theoretically based on a theoretical solution to the heat and mass transfer processes in the desiccant rotor. A simple correlation equation for the optimum rotation speed is derived to show the effects of various parameters including the thermo-physical properties, the geometric dimension, and the operating condition of the desiccant rotor. The theoretical result is compared with existing experimental data to validate the linearization and simplification included in the solution procedure. Based on the theoretical solution, the effects of major parameters on the optimum rotation speed are studied and the fundamental mechanism of the influences is investigated.